Your Language My Culture (YLMC): Developing a Local-Culture ELT Matrix for Schools in Terengganu, Malaysia - Zawiah Yahya; Noraini Ibrahim; Rashila Ramli; Noraini Md Yusof; Zarina Othman (Kajian Malaysia, 2017)
This paper outlines details of a local-culture matrix that maps the cultural content of a supplementary, local-culture-based three-year reading programme in English for secondary schools in Terengganu, Malaysia. The reading programme, called "Your Language My Culture" (YLMC), is designed by a group of researchers from Universiti Kebangsaan Malaysia (UKM) with the objective of upgrading both English proficiency and local culture awareness at the same time. Two broadly opposing views on the use of local culture in English Language Teaching (ELT) are presented: one that favours the use of "authentic" cultural norms of native speakers of English in a process of "cultural assimilation"; the other that favours localising materials for ELT textbooks adapted to the local environment of English as a Second Language (ESL) learners. The YLMC programme adopts the latter view on the conviction that the learners' familiarity with local content and context will better facilitate learning and interaction with English. In the design of the culture matrix for ELT, the YLMC team has also taken cognizance of the global trends in pedagogy and the specific context of Terengganu where the programme is implemented.